MAKNA KISAH NUH AS DALAM AL-QUR’AN (PERSPEKTIF HERMENEUTIKA FILOSOFIS) - Rusydi, Muhammad (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2017)
The writing discusses story of Noah (peace be upon him) in the Quran. The story will be approached by philosophical hermeneutics is conceived by Heiddegger and Gadamar. The main questions of the article are why and how the meaning of the story for Arabic people especially and for Moslem (human kind) generally. Finally, the result shows that Prophet Nuh is one of important ancestors for Arabic people and those people had listened and seen some historical events related to this prophet and his people. Moreover, the story teachs human being to surrender to Allah as it will lead them to appreciate all creations in this universe.